2012
DOI: 10.1074/jbc.m111.331611
|View full text |Cite
|
Sign up to set email alerts
|

Increased Laforin and Laforin Binding to Glycogen Underlie Lafora Body Formation in Malin-deficient Lafora Disease

Abstract: Background: Laforin deficiency causes glycogen hyperphosphorylation, which converts glycogen to aggregate-prone poorly branched polyglucosans. Malin deficiency also causes polyglucosans. Results: Malin deficiency increases total and glycogen-associated laforin, which renders glycogen aggregate-prone and poorly branched. Conclusion: Malin deficiency causes polyglucosans through increased laforin. Significance: Phosphate and laforin (and perhaps other proteins) must be cleared to enable normal glycogen construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 37 publications
(67 reference statements)
2
29
0
Order By: Relevance
“…Precisely why GS2 and PTG lead to normal glycogen rather than PBs is unclear, but in any case it is clear that increased GS1 is associated with PB formation. This result is consistent with the massive presence of GS1, and no other tested enzymes of glycogen metabolism, in LB isolated from mouse models of LD (10, 31, 34, 36-37). …”
Section: Resultssupporting
confidence: 88%
“…Precisely why GS2 and PTG lead to normal glycogen rather than PBs is unclear, but in any case it is clear that increased GS1 is associated with PB formation. This result is consistent with the massive presence of GS1, and no other tested enzymes of glycogen metabolism, in LB isolated from mouse models of LD (10, 31, 34, 36-37). …”
Section: Resultssupporting
confidence: 88%
“…Studies in LD mouse models revealed the presence of higher levels of covalently bound phosphate in LD muscle and brain glycogen (Nitschke et al, 2013, 2017; Tagliabracci et al, 2007). This is not surprising in laforin (phosphatase)-deficient Epm2a −/− mice but is intriguing in malin-deficient Epm2b −/− mice, where glycogen phosphate levels are intermediate between wild-type (WT) and Epm2a −/− levels (DePaoli-Roach et al, 2015; Tiberia et al, 2012). Increased phosphate has been hypothesized to be inseparably associated with the cause(s) of glycogen insolubility and precipitation in LD (Roach, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Lafora disease there is evidence that lack of laforin, which functions to remove phosphate from glycogen, or deficient removal of laforin from glycogen by malin makes the glycogen prone to aggregation as polyglucosan (Tiberia et al 2012). An imbalance of the activities of branching enzyme and glycogen synthase has been proposed as important for polyglucosan formation in equine polysaccharide storage myopathy (PSSM1) that is due to hyper-activity of glycogen synthase ( GYS1 ) secondary to a dominant missense variant (McCue et al 2008).…”
Section: Discussionmentioning
confidence: 99%